2018
DOI: 10.1016/j.mehy.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Could reflex cough induced through nebulized capsaicin achieve airway clearance in patients with acute retention of lung secretions?

Abstract: Nasotracheal suctioning (NTS) is a procedure commonly performed by respiratory physiotherapists and nurses to remove excess respiratory secretions from the tracheobronchial tree in a self-ventilating, non-intubated and non-tracheotomized patient. NTS is an important treatment modality for patients with acute secretion retention who are at high risk of progressive respiratory deterioration and arrest. However, NTS is a blind invasive procedure with risk of serious adverse events, and the patient experience of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…A study of acute stroke patients showed that capsaicin-induced reflex cough produced a higher maximum PCF than spontaneous cough (Kulnik et al, 2015), indicating that induced reflexive coughing is more effective than spontaneous cough in expelling respiratory secretions. After the cough is induced by capsaicin nebulization, the patient can use the chest wall oscillation and the rapid expiratory airflow produced by the cough to move secretions from the deep small airways into the major airway at once (Kulnik, 2018). Accordingly, the daily sputum output in the intervention group was significantly higher than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study of acute stroke patients showed that capsaicin-induced reflex cough produced a higher maximum PCF than spontaneous cough (Kulnik et al, 2015), indicating that induced reflexive coughing is more effective than spontaneous cough in expelling respiratory secretions. After the cough is induced by capsaicin nebulization, the patient can use the chest wall oscillation and the rapid expiratory airflow produced by the cough to move secretions from the deep small airways into the major airway at once (Kulnik, 2018). Accordingly, the daily sputum output in the intervention group was significantly higher than that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this may be related to the disease characteristics of patients with cerebral hemorrhage. Capsaicininduced cough is based on the function of a well-integrated cough reflex pathway (Kulnik, 2018), which could be interrupted if there is a dysfunction at any point in the neural pathways. The cough reflex in stroke patients is compromised because of brain lesions, resulting in decreased cough sensitivity (Hegland et al, 2016;Zhao et al, 2015), and that tracheotomy disrupts the physiology of the airway, further weakening the cough reflex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations